Burden of stroke incidence among atrial fibrillation, valvular heart disease and coronary heart disease patients. (11th May 2022) - Robinson, K; Katzenellenbogen, JM; Kleinig, T; Kim, J; Budgeon, C; Thrift, A; Nedkoff, L
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Health and Medical Research Council of Australia Background: The public health burden of stroke has continued to increase in recent decades. In patients with cardiac disease, the risk of stroke is 2-4 times higher than in the general population, and therefore investigating stroke incidence in these patients is important for identifying opportunities for stroke prevention. Purpose: We aimed to measure the incidence of stroke in people with atrial fibrillation (AF), valvular heart disease (VHD) or coronary heart disease (CHD) to assess the risk of stroke by age, sex, pre-existing vs new cardiac disease, and nonfatal/fatal status. Methods: We used a person-linked hospitalisation/mortality dataset to identify all people hospitalized with AF, VHD or CHD from 1985 to 2017 in a whole-population setting. These cardiac cases were stratified as pre-existing (hospitalised between 1985 and 2012, who were alive at 31st October 2012 with no history of stroke) or new (first-ever cardiac hospitalisation from November 1st, 2012 to October 31st, 2017, with no prior hospitalisation for AF, VHD or CHD, and no history of stroke). Patients aged 20-94 years were included in the study. Pre-existing and new cardiac cases were followed over the 5-year study period (1st November 2012 to 31st December 2017) to identify first-ever stroke events. Age-specific and age-standardised rates (ASR) for stroke incidence were calculated for all cardiac cases combined, and separately for pre-existing and new cases. Results: The cohort comprised 175, 560 patients. The majority of the cohort had a single cardiac condition (55.7% CHD; 23.0% AF; 5.0% VHD), while 16.3% of patients had multiple cardiac conditions. There were 5, 871 (3.3%) first-ever strokes (5.2% in AF patients, 4.0% in VHD, 2.8% in CHD). Stroke incidence ASRs were greater in women than men across each cardiac group and irrespective of the presence of single or multiple cardiac conditions (Figure). This was largely driven by women aged ≥75 years, with stroke incidence being greater in women than men in each cardiac group. In women aged 20-54 years, there was a 4.9-fold higher incidence of stroke in those with multiple versus single cardiac conditions, and this differential appeared to decline with increasing age (Figure). Incidence of non-fatal strokes was greater than fatal stroke in all age groups except among 85-94 year olds. Incidence rates in each cardiac group were between 1.2 and 2.4 times higher in those with new versus pre-existing cardiac disease. Conclusions: Stroke incidence is substantial in patients with cardiac disease. Older women with AF and VHD had the highest stroke rates overall, although younger patients with multiple cardiac conditions were also at high risk. These cardiac patients should be targeted for evidence-based management to minimise their stroke risk, especially in the period immediately following diagnosis when risk is highest. Figure Legend. Age-specific and age-standardised stroke incidence rates in all cardiac cases.